2013
DOI: 10.1007/s10597-013-9674-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial Coping Strategies of Mental Health Consumers: Managing Social Benefits

Abstract: Mental health consumers depend on social benefits in the forms of supplemental security income and social security disability insurance for their livelihood. Although these programs pay meager benefits, little research has been undertaken into how this population makes ends meet. Using a qualitative approach, this study asks what are the financial coping strategies of mental health consumers? Seven approaches were identified: subsidies, cost-effective shopping, budgeting, prioritizing, technology, debt managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…A few studies have examined the way in which poor people with SMI describe how they have been able to manage outside psychiatric institutions when faced with this double trouble. Ware and Goldfinger ( 1997 ), Wilton ( 2004 ), Caplan ( 2014 ) and Topor et al ( 2014 ) reported similar findings in different socio-political contexts. The individuals they studied had developed both personal and collective ways of coping with financial constraints.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…A few studies have examined the way in which poor people with SMI describe how they have been able to manage outside psychiatric institutions when faced with this double trouble. Ware and Goldfinger ( 1997 ), Wilton ( 2004 ), Caplan ( 2014 ) and Topor et al ( 2014 ) reported similar findings in different socio-political contexts. The individuals they studied had developed both personal and collective ways of coping with financial constraints.…”
Section: Introductionmentioning
confidence: 63%
“…Persons with SMI deal with poverty in different ways (Caplan 2014 ), and if their economic conditions improve this makes it possible for them to deploy strategies that enhance their everyday lives and transform their longing for social intercourse into goal-directed practices in the form of personal projects.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health service users who receive public benefits such as Medicaid, Supplemental Security Income and Social Security Disability Insurance live on an extremely limited income and have considerable difficulty meeting their material needs (Kessler et al, 2008; Wilton, 2003). They employ various coping and survival strategies, including cost-effective shopping, budgeting, prioritizing, and saving money (Caplan, 2014). The evidence here indicates that self-directing participants incorporate a range of such strategies into their budgeting and planning process.…”
Section: Discussionmentioning
confidence: 99%
“…Counselors might ask clients how they are making the most of their challenging circumstances or what motivates them to continue trying to cope amidst such challenges. Financial coping among the poor illustrates the strengths inherent in how people make ends meet (Caplan, ). Caplan () identified seven financial coping strategies in a study of individuals with mental illness receiving Supplemental Security Income: (a) using outside subsidies/programs, (b) cost‐effective shopping, (c) prioritizing expenditures, (d) budgeting, (e) using technology (e.g., paying bills online at the local library), (f) limiting debt, and (g) actively attempting to save money.…”
Section: I‐care Modelmentioning
confidence: 99%